Effect of Solitary and Group Purposeful Movement Plays on Various Aspects of Theory of Mind in Girls Aged 8 years - Narges Borhani Dizaji; Shahab Parvinpour; Saleh Rafiee (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims Solitary movement plays have been reported to be effective in improving the primary aspects of Theory of Mind (ToM), and the design of interventions based on interpersonal interactions has been emphasized to influence the advanced aspects of ToM. To test this hypothesis, the effect of solitary and group purposeful movement plays on various aspects of ToM in girls aged eight years was compared. Methods In this quasi-experimental study with pre-test and post-test design, 40 girls with a mean age of 8.53 years from two elementary schools in Tehran were selected and randomly assigned to solitary play (n =13), group play (n = 12), and control (n = 15) groups after preliminary evaluations. The Test of Theory of Mind (Ghamrani et al., 2006) was completed immediately before and after an experimental period (eight weeks, 16 sessions of 60 minutes) and one month after the end of the intervention. The 3 (time) × 3 (group) mixed analysis of variance and related post hoc tests at a 95% confidence level were used to analyze the data. Results Recognition of emotions and pretense (ps < 0.001), understanding of false belief (ps <0.001), and total level of ToM (ps < 0.001) significantly improved in both experimental conditions, but second-order false belief and understanding of humor improved only in the group play condition (p < 0.001). Furthermore, the scores of the recognition of emotions and pretense (ps < 0.05), understanding of false belief (ps < 0.05), second-order false belief and understanding of humor (ps < 0.001), and the total level of ToM (ps < 0.001) in the play condition group were significantly higher than solitary play in the post-test and follow-up. Conclusion Although solitary movement plays improve the primary aspects of ToM, to facilitate the development of more advanced aspects, such as understanding of humor and second-order false belief, the use of group-based interactive-cooperative plays seems to be essential for eight-year-old girls.